Bioeconomic Analysis of Stolephorus sp Fisheries in the Conservation Area of Perairan Karang Jeruk, Tegal Regency, Central Java - Esza Cahya Dewantara; Achmad Fahrudin; Yudi Wahyudin (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
The goal of this study was to determine the utilization level of anchovy resources in Perairan Karang Jeruk after being designated as a fisheries reserve conservation area. The CYP algorithm approach was used as a bioeconomic analysis. This study was conducted in November 2019 – January 2020. The results showed that the intrinsic growth rate of anchovies (r) was 1.803 tons/year, the capture coefficients (q) was 0.000506 tons/trip, and the environment supporting capacity (K) amounting to 1501.67 tons/year, cost (c) of 0.27 million/trip and price (p) of 8.73 million/ton. MSY efforts (EMSY) amounted to 1780.42 with maximum production (hMSY) of 676.80 tons/year. MEY (EMEY) efforts amounted to 1694.14 with maximum production (hMEY) of 675.21 tons/year. The utilization of fisheries resources activities shows more capture, both biologically and economically. Policy recommendations that can be applied from the results of the study are that business/effort limitations need to be made to 2416 – 2539 trip/year for payang fishing gear and 1489 – 1565 for Mini Purse Seine fishing gear. The implementation of the quota system on the Total Allowable Catch (TAC) basis for payang fishing gear is 65.52 tons/year, while the mini purse seine fishing gear is 475.92 tons/year.